Analisis Sensitivitas Premi Asuransi Jiwa Berjangka terhadap Suku Bunga dengan Model CIR Berdasarkan Volatilitas & Waktu - Putri Yusra Haliza; Auta Shintha Sarah; Agnes Monica Simorangkir (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the sensitivity of term life insurance premiums to interest rate changes using the Cox-Ingersoll-Ross (CIR) model by considering volatility and coverage period. The study uses interest rate data for the 2021–2025 period obtained from the Central Statistics Agency (BPS) and the 2019 Indonesian Mortality Table (TMI), with a case study of a 30-year-old insured, a sum insured of IDR 100,000,000, and tenors of 5, 10, and 20 years. The results show that the premiums of the CIR model are consistently higher than those of the fixed interest rate model by a difference of around 0.5%–1.5%. Quantitatively, an increase in the interest rate from 3% to 7% significantly reduces the premium, while an extension of the coverage period increases the premium proportionally. Meanwhile, interest rate volatility has a relatively small effect on the premium, in line with the low value of the volatility parameter (σ = 0.00549). Thus, interest rates and coverage terms are the dominant factors in determining premiums, while volatility has a limited influence in the model used.